Penguatan Kompetensi Guru Sekolah Menengah Pertama Di Kota Surakarta Dalam Pembuatan Bahan Ajar Digital Dengan Aplikasi Kvisoft Di Masa Pascapandemi - Budhi Setiawan; Kundharu Saddhono; Raheni Suhita; Muhammad Aditya Wisnu Wardana (Jurnal Kabar Masyarakat, 2023)
In facing the challenges of distance learning caused by the COVID-19 pandemic, teachers at SMP Negeri 1 Surakarta have worked to improve their skills in producing attractive and interactive digital teaching materials. Through training and workshops, teachers master the use of the Kvisoft application to create digital teaching materials that suit students' needs. This study uses a qualitative approach involving the participation of teachers as research subjects. The results of the study show that strengthening teacher competence in making digital teaching materials has a positive impact on learning. Teachers who are skilled in using the Kvisoft application are able to create teaching materials that are interesting, interactive, and according to the needs of students. Thus, strengthening teacher competence in making digital teaching materials with the Kvisoft application makes an important contribution in improving the quality of learning at SMP Negeri 1 Surakarta in the post-pandemic era. This article provides a deeper understanding of the importance of strengthening teacher competency in the production of digital teaching materials and provides practical guidance for schools and teachers in adopting this technology.